2020
DOI: 10.2147/dmso.s235015
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Postural Stability and Transverse Abdominal Muscle Activity in Overweight Post-Stroke Patients: A Prospective, Observational Study</p>

Abstract: Purpose: Post-stroke hemiparesis has a significant impact on postural stability. The transversus abdominis (TrA) muscle contributes to the stability of the spine. The aim was to assess both the postural stability and the activity of the TrA muscle in overweight post-stroke patients. Methods: A group of 56 participants (61.12 ± 11.5 years) was divided into the study group (n=28 post-stroke patients, 63.7 ± 10.9 years) and control group (n= 23 healthy participants (58.5 ± 12.2 years). The Berg Balance Scale (BBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The BBS is used in clinical practice and shows that it is reliable, valid, and sensitive. It is currently the most widely used clinical balance scale at home and abroad ( 44 ). Functional Reach Test (FRT) assesses the maximum distance that the participant stretches forward beyond the arm length, while the patient maintains a fixed standing position during the test ( 45 ); the average of the two trials will be used; a higher score indicates better balance ability ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…The BBS is used in clinical practice and shows that it is reliable, valid, and sensitive. It is currently the most widely used clinical balance scale at home and abroad ( 44 ). Functional Reach Test (FRT) assesses the maximum distance that the participant stretches forward beyond the arm length, while the patient maintains a fixed standing position during the test ( 45 ); the average of the two trials will be used; a higher score indicates better balance ability ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…The possibility to control a stable body posture is the basis for independent mobility and it is extremely important to performing daily activities [43]. In our study, very low IADL scores before the intervention (mean IADL = 11.9) were recorded.…”
Section: Discussionmentioning
confidence: 56%
“…According to published clinical and basic studies, skeletal muscle injury after stroke primarily occurs in the transverse muscle [ 47 ]. Therefore, we refer to the studies from transverse muscle atrophy [ 48 ], including the treadmill and pull tests [ 49 ]. In this study, we found that the pathological alteration of endurance and exercise in animals under the MCAO model was not synchronized.…”
Section: Discussionmentioning
confidence: 99%